2014
DOI: 10.12982/cmujns.2014.0054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watermelon (Citrullus lanatus) Flesh Extract on Sexual Behavior of Male Rats

Abstract: The effects of red watermelon (Citrullus lanatus) flesh extract on male sexual behavior as well as its adverse effects were investigated using animal models. The suspension of the flesh extract was administered orally at doses of 100, 500 and 1000 mg/kg to different groups of male rats (n = 5) daily for 22 days. The receptive female rats were prepared by hormonal treatment. The mating behavior was investigated and compared with the standard reference drug, sildenafil citrate. The adverse effects of the plant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
1
8
0
4
Order By: Relevance
“…Allium cepa contains selenium, copper and zinc whereas Moringa oleifera contains lavonoids, anthraquinone glycosides, tannic acid, carotene and glucose which can be responsible for aphrodisiac activity(activity (Allouh et al, 2014). Water melon contains arginine and citralline, dragon fruit which contains β-sitosteron and α-β-amyrin and celery contains valerophenone, 1-dodecanol, 9-octadecanonic acid and methyl ester helps to improve aphrodisiac activity (Munglue et al, 2014;Hardani et al, 2015;Kanedi, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allium cepa contains selenium, copper and zinc whereas Moringa oleifera contains lavonoids, anthraquinone glycosides, tannic acid, carotene and glucose which can be responsible for aphrodisiac activity(activity (Allouh et al, 2014). Water melon contains arginine and citralline, dragon fruit which contains β-sitosteron and α-β-amyrin and celery contains valerophenone, 1-dodecanol, 9-octadecanonic acid and methyl ester helps to improve aphrodisiac activity (Munglue et al, 2014;Hardani et al, 2015;Kanedi, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the mount frequency, intromission frequency and ejaculation latency 1 (ejaculation latency in irst series) has increased for the highest concentration of dose mount latency, intromission latency, ejaculation latency and ejaculation interval was increased at the lowest concentration. There was a negative results for the increase in body weight and reproductive organ weight (Munglue et al, 2014) .…”
Section: Citrullus Lanatus (Watermelon) (Cucurbitaceae) Figure 11: CImentioning
confidence: 91%
“…Semangka merupakan buah yang mengandung senyawa arginin dan sitrulin. Kandungan sitrulin dalam buah semangka dikenal luas berperan penting dalam meningkatkan produksi nitric oxyde (NO) sehingga menyebabkan terjadinya ereksi (Munglue et al, 2014). Nitric oxide berdifusi ke dalam otot polos sel vaskular dalam corpus cavernosum penis, sehingga menstimulasi pelepasan guanylyl cyclase dan meningkatkan cyclic guanosine mono phosphate (cGMP).…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian Munglue et al (2014) dosis efektif buah semangka untuk tikus adalah 1000 mg/kgBB maka variasi dosis pada penelitian ini adalah 500, 1000, dan 2000 mg/kgBB. Dosis pemberian infusa dihitung berdasarkan variasi dosis tersebut.…”
Section: Rancangan Dosisunclassified
See 1 more Smart Citation